Lazer: a perspectiva dos moradores no município de Duque de Caxias - RJ - Moraes, Carlos Eduardo Sorrentino (2011)
This dissertation aims to find the standard of choice for residents of Duque de Caxias in relation to the provision of leisure products and services available in the city and the metropolitan area of Rio de Janeiro. Considering the relationship between city, citizenship and quality of life in the municipality of Duque de Caxias, in the outskirts of the metropolitan area - Rio de Janeiro, there is a non-availability of urban facilities and lack of territorial planning capable of meeting the human needs of the population the site. Economic development in the city led to the deployment process of industrial complexes in the region, accelerating the urbanization phenomenon and creating a large deficit in the supply of public policies such as safety, health and leisure services to its residents. Through application of field research, by providing access to interactive media, we interviewed twenty residents of the municipality about their preferences and habits related to leisure. Based on the technique of content analysis, we found that respondents to the leisure activities that seek within the municipality where they reside are mainly linked to corporate interests. For options related to nightclubs and restaurants, the small number of options available to residents, no matter how good in quality, seeks to make in nearby towns. It follows then, that it is necessary to invest in quality entertainment options for leisure-oriented and intellectual, since they are almost nonexistent.